1984
DOI: 10.1136/vr.114.26.635
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of ruminants in some Caribbean and South American countries for type-specific antibody to bluetongue and epizootic haemorrhagic disease viruses

Abstract: The results of a serological survey of ruminant livestock in some countries of the Caribbean and South America for type-specific antibody to bluetongue virus are reported. Using the microneutralisation test with the international serotypes 1 to 22 of bluetongue virus, antibodies to several types were detected. Analysis of the data indicated that in 1981-82 bluetongue virus types 6, 14 and 17, or viruses closely related to them, were infecting ruminants in this region of the world. Antibody to the related virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…The presence of antibodies to BT types 12, 14 and 17 and EHD types 1 and 2 in northern Colombia is consistent with previous findings of antibody to the same types of BT, and EHD type 2 in the Caribbean islands, and types 14 and 17 and EHD types 1 and 2 in Guyana and Suriname (Gumm et al 1984). These authors also found antibodies to BT types 1 and 6.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The presence of antibodies to BT types 12, 14 and 17 and EHD types 1 and 2 in northern Colombia is consistent with previous findings of antibody to the same types of BT, and EHD type 2 in the Caribbean islands, and types 14 and 17 and EHD types 1 and 2 in Guyana and Suriname (Gumm et al 1984). These authors also found antibodies to BT types 1 and 6.…”
Section: Discussionsupporting
confidence: 91%
“…EHD virus has been isolated from cattle in the United States and Canada (Sellers, 1981). In the American tropics antibody to EHD has been detected in cattle in the Caribbean islands, Guyana and Suriname (Gumm et al, 1984) and Costa Rica (Homan & Taylor, unpublished observations). EHD and BT viruses are antigenically differentiable by neutralization tests, but in tests detecting group-specific antibody, such as agar gel precipitation, varying degrees of cross-reaction may occur (Jochim, 1976;Della-Porta, McPhee & Parsonson, 1983).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations